Quantitative evaluation of eggs freshness using flash thermography. Issue 1 (2nd January 2020) - Freni, F.; Quattrocchi, A.; Piccolo, S. A.; Montanini, R.
ABSTRACT: The paper examines the topic of identifying eggs freshness through an original approach based on pulsed thermography. The proposed method relies on a short thermal stimulation performed by means of a xenon flash, which rises up the temperature of the egg of less than 1°C. The entire process requires about 1 s, thus providing an effective quality control tool for assessing the freshness of eggs intended for human consumption. The identification and evaluation procedure has been automated by developing a dedicated image processing algorithm, based on a morphological operator with 'white top hat' transformation. The software performs a series of preliminary operations on the acquired thermograms and returns an estimation of the air chamber projections, that are correlated to egg degradation and weight reduction.